2019
DOI: 10.1080/10408398.2018.1487927
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Melatonin: A mechanistic review

Abstract: N-acetyl-5-methoxy-tryptamine (melatonin) is a natural substance produced both by plants, as a secondary metabolite, and animals, by the pineal gland and other tissues. In humans, melatonin participates in numerous functions including the regulation of mood, sleep, reproduction, promotion of immunomodulation, antioxidant defense and as an anti-inflammatory agent. The anti-inflammatory activity of melatonin could yield beneficial effects on intake, particularly against the chronic inflammation which underlies m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 118 publications
0
88
0
12
Order By: Relevance
“…It is thought that memantine‐mediated suppression of oxidative stress underlies its anti‐inflammatory effects . It is well documented that melatonin possesses anti‐inflammatory properties, based generally on its antioxidant action (for review). Previous studies have established the ability of melatonin to inhibit nuclear factor‐kappa B (NF‐κB) and cyclooxygenase (COX)‐2, to prevent activated microglia‐induced production of proinflammatory cytokines and to reduce Aβ‐induced secretion of interleukins IL1‐β and IL‐6 in transgenic mouse models thereby protecting the brain …”
Section: Discussionmentioning
confidence: 99%
“…It is thought that memantine‐mediated suppression of oxidative stress underlies its anti‐inflammatory effects . It is well documented that melatonin possesses anti‐inflammatory properties, based generally on its antioxidant action (for review). Previous studies have established the ability of melatonin to inhibit nuclear factor‐kappa B (NF‐κB) and cyclooxygenase (COX)‐2, to prevent activated microglia‐induced production of proinflammatory cytokines and to reduce Aβ‐induced secretion of interleukins IL1‐β and IL‐6 in transgenic mouse models thereby protecting the brain …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that melatonin can play a key role in plant protection against biotic stress. melatonin has been reported to have immunomodulatory, antioxidant, anti-inflammatory, and neuroprotective activities in animals [31][32][33][34], so it can be applied as an effective therapeutic substitute for the suppression of microbial diseases. On the other hand, recently, many important findings have shown the beneficial effect of melatonin in plant-pathogen interaction.…”
Section: Melatonin As An Alleviating Agent Against Plant Pathogensmentioning
confidence: 99%
“…Also, the strong inhibitory action of melatonin against Mycobacterium tuberculosis (H37Rv strain) was revealed after application of a 10 µM concentration; however, the combined application of melatonin with isoniazid inhibited the growth of bacteria three to four times more than any compound alone [53]. Besides its ability to potentiate immune responses, additional explanations have been provided to clarify the mechanism of melatonin's antibacterial action in animals, including cellular cAMP and Ca 2+ regulation, reduction of intracellular substrates, free radical formation, and binding to the bacterial cell wall, which causes cytoderm destabilization [32][33][34][35][36][37][38][52][53][54]. In plant-bacteria interaction, melatonin has presented effective antibacterial activities against phytobacterial pathogens.…”
Section: Melatonin Bioactivity Against Bacteriamentioning
confidence: 99%
“…36 This step also includes nutraceuticals such as riboflavin (B2), magnesium, and coenzyme Q10 for migraine patients as well as vitamin B12, liquorice root, and vitamin C for POTS patients. 35,42,48 It also may counteract tachycardia in POTS patients. 35,42,48 It also may counteract tachycardia in POTS patients.…”
Section: Treatmentmentioning
confidence: 99%
“…37,[44][45][46] Additionally, there is evidence that melatonin is beneficial for both migraine and POTS patients as it improves sleep and has antiinflammatory properties. 35,42,48 It also may counteract tachycardia in POTS patients. 35 While all of these complementary therapies are potential options for POTS and migraine patients alike, physical therapy and CBT are the most beneficial when headaches and dysautonomias are seen simultaneously.…”
Section: Treatmentmentioning
confidence: 99%